2000
DOI: 10.1007/bf02523660
|View full text |Cite
|
Sign up to set email alerts
|

The clinicopathological significance of preoperative serum-soluble interleukin-2 receptor concentrations in operable non-small-cell lung cancer patients

Abstract: Elevated preoperative serum-soluble IL-2R concentrations in patients with operable NSCLC reflect the occurrence of intrapulmonary metastasis. Preoperative examination of serum-soluble IL-2R concentrations may be valuable in the detection of the intrapulmonary metastasis preoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 33 publications
1
10
0
2
Order By: Relevance
“…In patients with malignant melanoma (Ottaiano et al 2006), head and neck cancer (Tartour et al 2001), non-small-cell lung cancer (Kawashima et al 2000) and nasopharyngeal carcinoma (Hsiao et al 2009) sIL-2R was proved to be the most precise marker associated with prognosis of local and distant recurrence. To the contrary, Lissoni et al (1990) did not state any correlation between the initial sIL-2R level and subsequent course and outcome in adult patients with cancer of lungs, larynx, bronchi, stomach and breast.…”
Section: Sil-2rmentioning
confidence: 99%
“…In patients with malignant melanoma (Ottaiano et al 2006), head and neck cancer (Tartour et al 2001), non-small-cell lung cancer (Kawashima et al 2000) and nasopharyngeal carcinoma (Hsiao et al 2009) sIL-2R was proved to be the most precise marker associated with prognosis of local and distant recurrence. To the contrary, Lissoni et al (1990) did not state any correlation between the initial sIL-2R level and subsequent course and outcome in adult patients with cancer of lungs, larynx, bronchi, stomach and breast.…”
Section: Sil-2rmentioning
confidence: 99%
“…However, the clinical and biological signiWcance of sIL-2R in lung cancer patients is unclear (Marino et al 1990;Yano et al 1996a, b). Kawashima et al (2000) reported that elevated preoperative serum sIL-2R concentrations in patients with operable NSCLC reXect the occurrence of intrapulmonary metastasis. In the present study, the serum sIL-2R concentrations in patients with NSCLC also exhibited a signiWcant elevation compared to those of healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23] Moreover, it has been demonstrated that high serum levels of interleukin 6, 19,24,25 interleukin 8, 26 interleukin 10, 27 vascular endothelial growth factor, 26,28 -30 soluble tumor necrosis factor receptors, 31 soluble ␣ interleukin 2 receptor 18 correlate with poor prognosis in patients with some malignant solid epithelial tumors and melanomas.…”
mentioning
confidence: 99%